"Chem Twist" for secondary/tertiary level education - Saraswathy Nalatambi, * (2012)
This study describes the effectiveness of “Chem Twist” in teaching and learning Chemistry at the secondary and tertiary level. “Chem Twist” is a multimedia game which enhances student’s engagement and their understanding on writing chemical formula. The objectives of this study are (i) to determine the relationship between student’s engagement and the designed multimedia game (ii) to determine students understanding on writing chemical formula. Visual basic network was used to design “Chem Twist”. “Chem twist” was designed to help students to adapt to all learning levels and help keep the classroom learning interactive and exciting. A Likert scale questionnaire is used to determine the relationship between student’s engagement and the designed multimedia game. Besides that, a set quiz questions is used to determine students understanding on the particular topic. The results will be discussed in the paper. The findings of this study provide further evidence in support of the significant effects of multimedia games on Chemistry students.